(untitled) (Jurnal Psikologi Integratif, 2019)
This study aims to see the influence of internal factors (self-regulated learning and mathematics anxiety) and external factors (mathematics teacher social support and peer social support) on mathematics learning achievement. This study uses a quantitative approach involving 169 students in junior high school students using purposive sampling technique. The results of the study concluded that there was an effect of self-regulated learning, mathematics anxiety, mathematics teacher social support, and peer social support simultaneously on mathematics learning achievement by 13.2%. The results of the t test showed that the variables of self-regulated learning and peer social support partially did not significantly influence mathematics learning achievement, in contrast to mathematics anxiety and mathematics teacher social support which partially had a significant effect on mathematics learning achievement. Penelitian ini bertujuan untuk melihat adamya pengaruh faktor internal (selfregulated learning dan kecemasan terhadap matematika) serta faktor eksternal (dukungan sosial guru matematika dan dukungan sosial teman sebaya) pada prestasi belajar matematika. Penelitian ini menggunakan pendekatan kuantitatif dengan melibatkan 169 siswa pada siswa sekolah menengah pertama dengan menggunakan teknik purposive sampling. Hasil penelitian menyimpulkan ada pengaruh self-regulated learning, kecemasan matematika, dukungan sosial guru matematika, dan dukungan sosial teman sebaya secara simultan terhadap prestasi belajar matematika sebesar 13.2%. Hasil uji t menunjukkan variabel self-regulated learning dan dukungan sosial teman sebaya secara parsial tidak berpengaruh secara signifikan terhadap prestasi belajar matematika, berbeda dengan kecemasan matematika dan dukungan sosial guru matematika yang secara parsial berpengaruh signifikan terhadap prestasi belajar matematika.